Statistical assessment of the impact of climate change on social and demographic processes (on the example of the Yaroslavl region) - V. V. Zholudeva (Статистика и экономика, 2019)
The purpose of this study is to analyze current global and regional climate changes, as well as a statistical assessment of the factors that cause climate change, on the one hand, and an assessment of the impact of climate parameters on the economy, agriculture and demographic processes using the example of the Yaroslavl region, on the other hand. The study was conducted on the example of the Yaroslavl region and covers the period from 1922 to the present. First of all, the article analyzes the regulatory documents on ecology and climate change. The insufficient attention of federal and local authorities to solving the above problems, the lack of regional strategies to prevent climate change and reduce its negative consequences, which leads to the increased socio-economic risks, is noted. In order to identify factors causing climate change, a correlation and regression analysis was performed. Regression models of the dependence of crop yields on the average annual air temperature and the average annual precipitation were constructed. The statistical base of the study was compiled by the data of the Federal State Statistics Service and the territorial body of the Federal State Statistics Service for the Yaroslavl Region, as well as GISMETEO data. Processing of the research results was carried out in Microsoft Excel and SPSS.During the study, it was found that in the Yaroslavl region there is an increase in average annual and average monthly air temperatures, as well as a slight increase in precipitation, which mainly occurs due to an increase in rainfall in spring and early summer.The anthropogenic factors that cause climate change, namely the burning of fossil fuels, an increase in industrial production, an increase in the number of vehicles, as well as a change in land use and deforestation, are identified and statistically substantiated.As a result of the study, it was found that changes in climatic parameters have an impact on the economy, agriculture and demographic processes, namely: – climate change has a positive effect on agricultural production. According to studies, an increase in average air temperature is a positive factor for the agricultural sector of the Yaroslavl region, as crop yields will increase with increasing air temperature. These trends need to be considered when choosing certain varieties of crops and selecting fertilizers. Increasing the level of management and the transition to more modern technologies will have a greater effect. The efficiency and productivity of agriculture, as well as the food security of the region, will depend on these decisions; – it was found that hydro meteorological factors have a negligible effect on the growth rate of gross regional product and food production; – a statistical study showed that in the Yaroslavl region the effects of climate change on demographic processes and human health are currently insignificant.The findings can be used to develop mechanisms for adaptation to climate change and can serve as a basis for further research in the field of studying the impact of climate change on socio-economic and demographic processes in the Yaroslavl region.